2020
DOI: 10.7150/jca.34793
|View full text |Cite
|
Sign up to set email alerts
|

Consistency Analysis of Programmed Death-Ligand 1 Expression between Primary and Metastatic Non-Small Cell Lung Cancer: A Retrospective Study

Abstract: Background: Programmed death-ligand 1 (PD-L1) expression in non-small cell lung cancer (NSCLC) is considered as a predictive biomarker of anti-PD-1/PD-L1 cancer therapies. However, the correlation of PD-L1 expression status between the primary and paired metastatic NSCLC is still not clear. The current study aims to address this specific issue. Materials and Methods: The PD-L1 expression of the primary and paired metastatic lesions from 110 patients with NSCLC was retrospectively evaluated by immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Kim instead observed higher concordance between the primary and metastatic NCSLC (concordance rate: 75.2%). Intermediate results were found by Xu 24 (concordance rate: 62.5%; k = 0.497) and Luo 25 (concordance rate: 61%; k = 0.39). These intermediate values were similar to those calculated in our series, although we considered only a limited number of cases (50 cases form 25 patients), independently from type, site, and time.…”
Section: Discussionmentioning
confidence: 79%
“…Kim instead observed higher concordance between the primary and metastatic NCSLC (concordance rate: 75.2%). Intermediate results were found by Xu 24 (concordance rate: 62.5%; k = 0.497) and Luo 25 (concordance rate: 61%; k = 0.39). These intermediate values were similar to those calculated in our series, although we considered only a limited number of cases (50 cases form 25 patients), independently from type, site, and time.…”
Section: Discussionmentioning
confidence: 79%
“…The Fleiss’ kappa statistic (FKS) was applied for the concordance analysis on the 2- and 4-category PD-L1 (SP142) IC scores 28 , 29 . FKS is an extension of Cohen’s kappa for three raters or more 30 . The FKS can be interpreted as “weak,” “moderate,” “strong,” and “near perfect” for its value in (0.4, 0.6), (0.6, 0.8), (0.8, 0.9), and (0.9, 1), respectively 11 , 31 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the process of collecting, processing and staining tissue blocks is not necessarily standardised across different sites and this can collectively influence test performance and accuracy. Direct comparison between different PD-L1 IHC assays suggests that individual tests cannot be interchangeably used in clinical practice (7), however other groups have shown that 22C3, 28-8, SP263 but not SP142 can be used interchangeably (8).…”
Section: Limitations Of Established and Emerging Immunotherapy Biomarkersmentioning
confidence: 99%